Influence of spontaneous fermentation leavens from cereal flour on the indicators of the technological process of making wheat bread - Hetman, Inna; Mykhonik, Larysa; Kuzmin, Oleg; Shevchenko, Anastasiia (My University, 2021)
The sugar-forming ability of oat and buckwheat flour was lower than in the control sample by 19.4% and 56.4%; autolytic activity by 36.9% and 43.1%; total gas formation by 31.1% and 38.6%, respectively. The decrease in enzymatic activity was due to differences in chemical composition and technology of preparation of cereals used to produce oatmeal and buckwheat flour. In mixtures of wheat flour with oat or buckwheat flour, the sugarforming ability was higher than in the control sample by 15.1% and 10.4%; gas-forming capacity by 12.7% and 7.3%, respectively. This was due to the effect of the active β-amylase of wheat flour on the smaller starch grains of cereal flour. It was established that after the fifth renewal of leaven from oat and buckwheat flour it could be used for bread making, as the quality of buckwheat and oat leavens was stabilized due to physicochemical parameters (acidity – 16.0-18.0 degrees, lactic acid bacteria activity – 45-60 min). The addition of the studied leavens in the amount up to 12% by weight of flour in the dough allowed obtaining products with organoleptic and physicochemical parameters close to the control sample.
Keywords: fermentation; leaven; dough; bread; кафедра технології хлібопекарських і кондитерських виробів; кафедра технології ресторанної і аюрведичної продукції; бродіння; тісто; закваска; хліб